Association of Notified Cases and Treatment Success Rates in Pulmonary Tuberculosis - Vallejos-Parás, Alfonso; Cabrera-Gaytán, David Alejandro; Padilla-Velázquez, Rosario; Arriaga-Nieto, Lumumba; Valle-Alvarado, Gabriel; Grajales-Muñiz, Concepción; Rojas-Mendoza, Teresita; Niebla-Fuentes, Maria del Rosario (Revista de investigacion clinica, 2018)
Background: Tuberculosis has long been recognized as a public health problem in large cities. The goals of the “Stop TB” strategy of the WHO specifically promote its study at the subnational level. Therefore, we aimed to describe the state of pulmonary tuberculosis (PTB) at the municipality level in Mexico. Methods: We obtained data on new cases of PTB and treatment success rates (TSRs) per municipality from each state in Mexico, reported by the Mexican Social Security Institute to the National Epidemiological Surveillance System during 2013. Regression model was used to quantify associations between PTB and TSR by the municipality. Results: We included 4090 cases of PTB distributed in 432 municipalities. There were 121 municipalities with TSRs < 85%. Lower TSRs were associated with older age, male sex, and comorbidities. Conclusions: Results suggest a negative outcome of PTB treatment in patients with HIV and in those with malnutrition. The number of reported cases by the municipality was not associated with a negative treatment outcome. (REV INVES CLIN. 2018;70:198-202)